2012
DOI: 10.1534/g3.112.003749
|View full text |Cite
|
Sign up to set email alerts
|

SlWUS1; An X-linked Gene Having No Homologous Y-Linked Copy inSilene latifolia

Abstract: The dioecious plant Silene latifolia has heteromorphic sex chromosomes, and comparison of the positions of sex-linked genes indicates that at least three large inversions have occurred during the evolution of the Y chromosome. In this article, we describe the isolation of a new sex-linked gene from S. latifolia, which provides new information on the evolution of this plant’s young sex chromosomes. By using reverse-transcription polymerase chain reaction degenerate primers based on the Arabidopsis thaliana sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
(94 reference statements)
1
19
0
Order By: Relevance
“…Our new map includes 11 genes whose X-linked copies have been genetically mapped: seven by Bergero et al 25 and four by Kazama et al 43 . The orders of these genes on the Y chromosome in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our new map includes 11 genes whose X-linked copies have been genetically mapped: seven by Bergero et al 25 and four by Kazama et al 43 . The orders of these genes on the Y chromosome in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When these studies were done, very few validated X-hemizygous genes were available in S. latifolia . Only two fully degenerated Y-linked genes in S. latifolia have so far been documented [ 27 , 28 ]. Two recent studies used segregation analysis in large families and inferred further X-hemizygous genes, one being a segregation analysis using RadSeq data [ 5 , 29 ]; however comparing these genes with the sex-linked contigs from RNA-seq studies reveals that ~57 % might be X/Y gene pairs, so we cannot use them as well-validated X-hemizygous genes (see the list of genes with X-hemizygous segregation patterns in Additional file 4 : Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…2012 ). The X-hemizygous gene SlWUS1 in Silene latifolia was shown (using qRT-PCR) to have lower expression levels in males than in females and to have both X copies expressed in females ( Kazama et al. 2012 ), therefore, the study concluded that there was no evidence that this gene was dosage compensated or X-inactivated.…”
Section: Introductionmentioning
confidence: 98%
“…From these four studies ( Bergero et al. 2015 ; Chibalina and Filatov 2011 ; Kazama et al. 2012 ; Muyle et al.…”
Section: Introductionmentioning
confidence: 99%